Proses Sosialisasi dan Pembelajaran Moral dalam Cerita 'Gbagba': Tinjauan Kritis melalui Teori Sosialisasi - Andi Nurul Annisa Yudha; Sawedi Muhammad; Rahmat Muhammad (Universitas Muhammadiyah Makassar, 2025)
Robtel Neajai Pailey was awarded the International Anticorruption Excelence Award for her book, Gbagba. The twin brothers are from the port city of Buchanan who will be on vacation to their family home in the capital Monrovia. In this story socialization takes place through their interactions with relatives and the new environment in Monrovia. Sunday Ma and Sunday Ga face direct examples in everyday life, the injustices they witness and actions that do not match the values that their oracles teach. Robtel Neajai Pailey's